Optimization and Enhanced Production of Hygromycin B Under Solid State Fermentation from Streptomyces hygroscopicus MTCC 1105 - Mahesh*, Narayanan; Balakumar, Srinivasan; Arunkumar, Mani; Seetha, Ganesan; Chitra, Padmanaban (Asian Journal of Chemistry, 2013)
In the current study, four substrates such as wheat rawa, bombay rawa, rice bran and barley were screened for the ability to produced hygromycin B under solid state fermentation. The substrates, bombay rawa produce the highest yield when compared to other substrate in solid state fermentation. The present research showed the maximum yield was obtained in bombay rawa as 966 μg/g. Similarly the moisture 60 % showed 495 μg/g, pH 7 as 451.2 μg/g, temperature 28 ºC produces 495 μg/g, incubation period 6 days of 552.6 μg/g, 1 % w/w soluble dextrose of 930 μg/g, yeast extract of 585 μg/g and ammonium sulphate of 586.8 μg/g were obtained and optimized. Antibiotic sensitivity test assay proved that both gram positive and negative microorganisms are sensitive to hygromycin B. Among the substrates, bombay rawa showed the maximum zone of inhibition in (35 mm) diameter against Klebsiella pneumoniae. These results showed the way to the pharmaceutical industries for the development of products under solid state fermentation.